Presynaptic CLC-3 Determines Quantal Size of Inhibitory Transmission in the Hippocampus - Riazanski, Vladimir (2011)
The absence of the chloride channel CLC-3 in Clcn3(−/−) mice results in hippocampal degeneration with a distinct temporal-spatial sequence reminiscent of neuronal loss in temporal lobe epilepsy. We examined how the loss of CLC-3 might impact GABAergic synaptic transmission in the hippocampus. An electrophysiological study of synaptic function in Clcn3(+/+) and Clcn3-(−/−) mice in hippocampal slices before the onset of neurodegeneration, revealed a significant decrease in the amplitude and frequency of mIPSCs. We found that CLC-3 colocalizes with the vesicular GABA transporter VGAT in the CA1 region of the hippocampus. Cl(−)-induced acidification of inhibitory synaptic vesicles showed a significant dependence on CLC-3 expression. The decrement in inhibitory transmission in the Clcn3(−/−) animals suggests a decrease in neurotransmitter loading of synaptic vesicles which we attributed to defective vesicular acidification. Our observations extend the role of Cl(−) in inhibitory transmission from that of a postsynaptic permeant species to a presynaptic regulatory element.